Pharmacists’ role in diabetes management for persons with lived experience of homelessness in Canada: A qualitative study - McSweeney, Breanna; Campbell, Rachel B.; Grewal, Eshleen K.; Campbell, David J. T. (Frontiers in Clinical Diabetes and Healthcare, 2022)
Persons with lived experience of homelessness face many challenges in managing diabetes, including purchasing and storing medications, procuring healthy food and accessing healthcare services. Prior studies have found that pharmacy-led interventions for diabetes improved A1C, and lowered blood pressure and cholesterol in general populations. This study evaluated how select pharmacists in Canada have tailored their practices to serve persons with lived experiences of homelessness with diabetes. We conducted a qualitative descriptive study using open-ended interviews with inner-city pharmacists in select Canadian municipalities (Calgary, Edmonton, Vancouver, and Ottawa). We used NVivo qualitative data analysis software to facilitate thematic analysis of the data, focusing on how pharmacists contributed to diabetes care for persons with lived experience of homelessness. These pharmacists developed diabetes programs after discovering an unmet need in the population. Pharmacists have the unique ability to see clients frequently, allowing tailored education and hands-on assistance with diabetes management. These pharmacists provided extra-ordinary care like financial and housing resources and many of them were uniquely embedded within other services for persons with lived experience of homelessness (i.e. housing and social work supports). Pharmacists reported struggling with balancing optimal medical care for individuals with the financial constraints of running a business. Pharmacists are vital members of the diabetes care team for persons with lived experience of homelessness. Government policies should support and encourage unique models of care provided by pharmacists to improve diabetes management for this population.